Correlation between nucleated red blood cells and pulse oxygen saturation in neonatal asphyxia - Gatot Irawan Sarosa; Farid A. Rahmadi; Muhammad Sholeh Kosim; Kamilah B. Rahardjani (Indonesian Pediatric Society, 2014)
Background Neonatal asphyxia is the major cause of neonatal death at a rate of approximately 23%. The incidence of asphyxia is higher in developing countries, due to limited availability of perinatology facilities. Hypoxia due to asphyxia is characterized by low pulse oxygen saturation (Sp02), which basic health care facilities are unable to monitor. The number ofnucleated red blood cells (nRBCs) in asphyxia increases in order to compensate for the hypoxia. Few studies have reported on nRBCs as they relate to pulse oxygen saturation in neonatal asphyxia. Objective To assess for a correlation between nRBCs and pulse oxygen saturation in neonatal asphyxia. Methods In this cross-sectional study, asphyxia was assessed by way of Apgar scores; pulse oxygen saturation was monitored by pulse oximetry; and nRBCs were determined by blood smears. Statistical analysis used was Spearman's test. Results Subjects were 41 neonates with asphyxia, 15 of whom had 5th minute Apgar scores S 6. Subjects with Apgar scores S 6 had significantly higher umbilical venous nRBC counts [20.0 (SD 13.09) /100 white blood cell] than subjects with Apgar score > 6 [8.81 (SD 8.71) /100 white blood cell] ; (P = 0.004). Subjects with Apgar S 6 had significantly lower 5th minute Sp02 values [76.46 (SD 6.17) %] than subjects with Apgar scores > 6 [87.03 (SD 6.29)]; (P < 0.0001). Spearmans' test revealed a significant correlation between higher nRBC counts and lower pulse oxygen saturation (r = -0.804; P<0.0001) . Conclusion In asphyxia neonatorum there is a correlation between umbilical vein nRBC counts and the 5th minute Sp02. As such, we recommend using nRBC examinations to predict pulse oxygen saturation as a means to assess the severity ofhypoxia in peripheral areas where pulse oximetry machines may be unavailable.